(untitled) (Bangladesh Journal of Medical Science, 2013)
Second most common oral disease next to dental caries is periodontal disease. It is considered to be inflammatory disorder that damages tissue through the complex interaction between periopathogens and the host defense systems. Researchers involved in periodontal disease diagnostics are currently investigating the possible use of oral fluids, such as saliva, for disease assessment. Secretions from the major salivary glands, which have a large number of proteins and peptides, are responsible for maintaining the integrity of the oral cavity. Also, because of its importance in oral biofilm formation and host defense, secreted saliva with its biomarkers may have a significant role in the establishment and progression of periodontal disease. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 244-249 DOI: http://dx.doi.org/10.3329/bjms.v12i3.15405